2001
DOI: 10.1067/mtc.2001.113020
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary metabolism of endothelin 1 during on-pump and beating heart coronary artery bypass operations

Abstract: Coronary artery bypass grafting with cardiopulmonary bypass is associated with an increase in systemic endothelin 1 levels. The mechanism involved is not related to a decreased pulmonary clearance of endothelin 1 from the systemic circulation but rather to an increased endothelin 1 release by the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
4
0
2
Order By: Relevance
“…Pulmonary ET-1 was also increased with CPB use, but similar effect was observed in off-pump group [11]. Increased levels of ET-1 were observed in both myocardial cells and myocardial circulation and attributed to CPB use [10,12].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Pulmonary ET-1 was also increased with CPB use, but similar effect was observed in off-pump group [11]. Increased levels of ET-1 were observed in both myocardial cells and myocardial circulation and attributed to CPB use [10,12].…”
Section: Introductionsupporting
confidence: 59%
“…Furthermore, they used immunohistochemical methods to test pulmonary ET-1 elimination, which was not decreased after CPB use. They concluded that increased systemic ET-1 levels were attributable to increased pulmonary production due to pulmonary endothelial dysfunction caused by CPB use [11]. In both groups of our patients, the observed nonsignificant initial increase in pulmonary ET-1 levels after anesthesia induction and sternotomy might be attributed to the use of inhalation anesthetics.…”
Section: Pulmonary Circulationmentioning
confidence: 51%
“…Bu nedenle KPB kullanılmadan 'off-pump' yapılarak oksidatif stres, enflamatuar yanıt gibi değişikliklerin azaltabileceği çeşitli yayınlarda da ortaya çıkarılmıştır (26)(27)(28)(29) . Çimen ve ark.…”
Section: Discussionunclassified
“…CPB is associated with significant pulmonary cytokine production (IL-8), neutrophil sequestration, and alveolar macrophage activation in clinical studies. [72][73][74] Pulmonary inflammation is associated with significant increases in static and dynamic elastance of the respiratory system and lung and work of breathing. 75 In a randomized trial, however, there was no difference between these parameters in on-or off-multivessel CABG.…”
Section: Pulmonary Injurymentioning
confidence: 99%